In vivo lung injury caused by Pseudomonas aeruginosa DNA - Al-Mathkhury, Harith (Iraqi Journal of Science, 2024)
Noticeable inflammatory reactions in rats lungs were caused by DNA isolatedfrom Pseudomonas aeruginosa include infiltration of macrophages, neutrophiles andlymphocytes. Additionally, fibromuscular hypertrophy of smooth muscles inrespiratory bronchiols was seen as well. Since lung homogenate shows no bacterialgrowth in all samples. Consequently, these inflammatory signs were attributed toDNA effect rather than any other cause. In conclusion, apart from live bacteria, P.aeruginosa DNA has the ability to cause inflammatory response in rat modelairways.